Azo-azomethine colorimetric chemosensors as molecular logic gates - Hamid Khanmohammadi; Romina Khanmohammadi (Heliyon)
The use of organic molecules as logic gates and their ability to simulate the performance of key components in integrated circuits has been one of the most challenging research areas over the past 30 years. Consequently, the design and application of new organic molecules successfully employed to simulate logic gates, switches, diodes, wires, and molecular keyboards are advancing rapidly, surpassing our imagination in terms of potential practical applications. This review focuses on providing an overview of reported colorimetric azo-azomethine chemosensors that have been utilized to simulate molecular logic gates and their complex circuits.